Endoscopic vacuum therapy for the treatment of Boerhaave syndrome: a multicenter analysis - Wannhoff, Andreas; Kouladouros, Konstantinos; Koschny, Ronald; Walter, Benjamin; Zoll, Zita Maria; Büringer, Karsten; Blank, Susanne; Schempf, Ulrike Beate; Caca, Karel; Wichmann, Dörte (Gastrointestinal endoscopy, 2025)
Background and Aims - Boerhaave syndrome, an effort rupture of the esophagus, is a rare but serious condition. Endoscopic vacuum therapy (EVT) is a new therapeutic approach for GI perforation. We aimed to evaluate EVT for treatment of Boerhaave syndrome. - Methods - This retrospective study was conducted at 5 tertiary hospitals in southern Germany. All patients treated for Boerhaave syndrome since 2010 were identified and included. Treatment success and outcomes were assessed and compared between the different modes of primary treatment. - Results - Fifty-seven patients with Boerhaave syndrome were identified (median age, 68 years; n = 16 female). The primary treatment was EVT in 25 cases, surgery in 14, and endoscopic stenting in 15. Primary EVT was successful in 20 (80.0%) of the 25 patients. Two patients were switched to surgical treatment, 1 was switched to esophageal stenting, and 2 patients died. The mortality rate was lower (P = .160) in patients treated primarily with EVT (n = 2 [8.0%]) compared with patients in the non-EVT group (n = 8 [25.0%]). Treatment success was significantly higher (P = .007) for primary EVT (80.0%) than for non-EVT (43.8%). Primary EVT was associated with treatment success in multivariable analysis. - Conclusions - EVT showed a high success rate for treatment of Boerhaave syndrome and was associated with treatment success.